Effect of vitamin D supplementation on N‐glycan branching and cellular immunophenotypes in MS. Issue 9 (23rd August 2020) - Bäcker‐Koduah, Priscilla; Infante‐Duarte, Carmen; Ivaldi, Federico; Uccelli, Antonio; Bellmann‐Strobl, Judith; Wernecke, Klaus‐Dieter; Sy, Michael; Demetriou, Michael; Dörr, Jan; Paul, Friedemann; Ulrich Brandt, Alexander
Abstract: Objective: To investigate the effect of cholecalciferol (vitamin D3) supplementation on peripheral immune cell frequency and N‐glycan branching in patients with relapsing‐remitting multiple sclerosis (RRMS). Methods: Exploratory analysis of high‐dose (20 400 IU) and low‐dose (400 IU) vitamin D3 supplementation taken every other day of an 18‐month randomized controlled clinical trial including 38 RRMS patients on stable immunomodulatory therapy (NCT01440062). We investigated cholecalciferol treatment effects on N‐glycan branching using L‐PHA stain ( phaseolus vulgaris leukoagglutinin ) at 6 months and frequencies of T‐, B‐, and NK‐cell subpopulations at 12 months with flow cytometry. Results: High‐dose supplementation did not change CD3+ T cell subsets, CD19+ B cells subsets, and NK cells frequencies, except for CD8+ T regulatory cells, which were reduced in the low‐dose arm compared to the high‐dose arm at 12 months. High‐dose supplementation decreased N‐glycan branching on T and NK cells, measured as L‐PHA mean fluorescence intensity (MFI). A reduction of N‐glycan branching in B cells was not significant. In contrast, low‐dose supplementation did not affect N‐glycan branching. Changes in N‐glycan branching did not correlate with cell frequencies. Interpretation: Immunomodulatory effect of vitamin D may involve regulation of N‐glycan branching in vivo . Vitamin D3 supplementation did at large not affect the frequencies of peripheral immune cells.